so we have f(g(x)) U=g(x) f'(U)*U*U' when, x=1, U=3 & U'=2 f'(3)*3*2 -4*3*2=-12 -12 is totally wrong apparently. Can someone please explain how its done? Thanks!
Follow Math Help Forum on Facebook and Google+
If this is graded homework, then it is our policy not to give an answer.
its not graded, I have unlimited attempts.
Do you know the "chain rule"? That is what is being tested here. Using your notation, with U= g(x), f(g(x))= f(U) and the derivative is f'(U)U', NOT the "f'(U)UU'" that you have.
Hello, Vamz! . . We have: . Then: . And: . . . . . . . . . . . . . . . . . . . - - - . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .
View Tag Cloud